Patterns of physical activity in children with haemophilia. (5th July 2012) - Broderick, C. R.; Herbert, R. D.; Latimer, J.; van, N.
Summary The current widespread use of prophylaxis in developed countries has enabled greater participation in physical activity. However, there are no data available on leisure‐time physical activity in Australian children with haemophilia. The data reported here were obtained from a case‐crossover study nested in a prospective cohort study of 104 boys with moderate and severe haemophilia followed for one year. Each child's physical activity was assessed using a modifiable physical activity questionnaire (Kriska's MAQ) administered at baseline, and a one‐week prospective activity diary at a randomly determined time. Children were aged 4–18 years. The median time spent in sport or leisure‐time physical activity in the preceding year was 7.9 h/week (IQR 4.6 to 12.9). The median time spent in vigorous physical activity was 3.8 h/week (IQR 1.6 to 6.4) and in moderate and vigorous physical activity 6.4 h/week (IQR 3.7 to 10.0). The median small‐screen time was 2.5 h/day (IQR 0.5 to 2.5). Forty‐five per cent of all children and 61% of children over the age of 10 years played at least one competitive sport. Averaged across one week, 43% of all children met the Australian government physical activity guidelines for children and 36% met the guidelines for small‐screen time. This study provides the first data regarding leisure‐time physical activity in children with haemophilia living in Australia. The majority of Australian children with haemophilia are not meeting the national physical activity and small‐screen time guidelines.